2019
DOI: 10.1109/access.2019.2944759
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite Tracking Consensus Control of Nonlinear High-Order Multi-Agent Systems Subject to Exogenous Disturbances

Abstract: This study concentrates on the bipartite tracking consensus for nonlinear high-order multi-agent systems(MASs) subject to exogenous disturbances over a signed directed graph. First, under the condition of nonlinear dynamics, two new control protocols are proposed to guarantee high-order bipartite tracking consensus under two cases with and without exogenous disturbances, respectively. Second, a disturbance observer is designed to estimate the external disturbances which originated from an external system. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Remark 2: By reviewing the literature (Jiang and Zhang, 2016; Jiang et al, 2016a, 2016b, 2017a, 2017b, 2018), it is found that the control for sign-consensus has been guaranteed in a group of linear agents under the static and dynamic control strategies. Likewise, control schemes for the nonlinear multi-agents undergoing signed communication graph have been investigated in the literature but for bipartite consensus problem (Ren et al, 2020, Wang et al, 2019, Yu et al, 2018, Zhang et al, 2020b). The bipartite consensus control design imposes a restriction on underlying communication graph to be structurally balanced along with directed spanning tree condition.…”
Section: Resultsmentioning
confidence: 99%
“…Remark 2: By reviewing the literature (Jiang and Zhang, 2016; Jiang et al, 2016a, 2016b, 2017a, 2017b, 2018), it is found that the control for sign-consensus has been guaranteed in a group of linear agents under the static and dynamic control strategies. Likewise, control schemes for the nonlinear multi-agents undergoing signed communication graph have been investigated in the literature but for bipartite consensus problem (Ren et al, 2020, Wang et al, 2019, Yu et al, 2018, Zhang et al, 2020b). The bipartite consensus control design imposes a restriction on underlying communication graph to be structurally balanced along with directed spanning tree condition.…”
Section: Resultsmentioning
confidence: 99%
“…Second, when considering the observer error between follower i and the leader, the requirement for state information of follower agent is relaxed, i.e., ni t ð Þ ¼ xi t ð Þ À s i x 0 t ð Þ, as we only require the state of the observer embedded in follower i. However, the state information of follower agent is necessary in existing related works [21,28,33]. Furthermore, our controllers could realize not only the common consensus but also the bipartite consensus involved with the competitive relationships between agents.…”
Section: Solve the Lmi As Followsmentioning
confidence: 99%
“…As an interesting issue continued from single systems, how to deal with exogenous disturbances, cyber-attacks and noises has received more and more attention recently [28]. In [29], the team-triggered fixed-time consensus control for a class of double-integrator agents under the uncertain disturbance was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study on the dynamic behaviour of MASs over signed graphs can be traced back to the seminal work on linear systems, in which the authors investigated how the network structure determines whether the system converges to a collective agreement or a polarized scenario, termed bipartite consensus [14]. Concerning leader-follower networks, we mention leader-follower bipartite consensus under fuzzy sliding mode control [15], nonlinear dynamics [16], adaptive control [17], and observer-based control [18].…”
Section: Introductionmentioning
confidence: 99%